Languages of Politics in Nineteenth-Century Britain
VIII, 255 p.
Keywords: A comprehensible and accessible portrait of the various 'languages' which shaped public life in nineteenth century Britain, covering key themes such as governance, statesmanship, patriotism, economics, religion, democracy, women's suffrage, Ireland and India.